Stiffness of connections of fast growing Eucaliptus Grandis with nails of small diameter - Piter, Juan Carlos Jesús (2018)
The stiffness of joints of fast-growing E. grandis with 2.5mm-diameter nails was investigated through an empirical research project carried out according to European standards. The results confirmed the effectiveness of the criterion adopted by the European design rules for calculating the instantaneous slip modulus in joints loaded parallel to the grain and exhibiting the recommended spacing and end distances. The empirical results also revealed that the stiffness of the connections was related to the angle of load to grain, which is not taken into account by the European criterion. An important decrease of the slip modulus was found in joints loaded perpendicular to the grain